Transcriptomic Analysis of the Liver Redox Response During Food-Anticipatory Activity Under a Time-Restricted Feeding Protocol in Rats - Adrián Báez-Ruiz; Andy Hernández-Abrego; Mauricio Díaz-Muñoz; Isabel Méndez (Antioxidants, 2025)
Daytime-restricted feeding (TRF) exerts outstanding effects on circadian physiology, nutrient utilization, and energy metabolism. Limiting feeding access to two hours during the daytime (12:00–14:00 h) for three weeks promotes food-anticipatory activity (FAA). FAA encompasses not only behaviors related to meal expectations but also includes diurnal fluctuations in liver metabolic responses, including distinct redox handling. Hepatic microarray profiles of genes associated with redox response processes were analyzed at three crucial time points: at the beginning of the light period or before FAA (08:00 h), during the expression of FAA (11:00 h), and after feeding (14:00 h). Data on fasting and nutrient processing were integrated, whereas circadian implications were extrapolated by comparing the TRF transcriptional output with a one-day fasting group. Transcripts of redox reactions, such as reactive oxygen species (ROS) generation, antioxidant defenses, NAD+/NADH equilibrium, and glutathione, hydrogen peroxide (H2O2), arginine, nitric oxide (NO), and hydrogen sulfide (H2S) metabolism, were analyzed. Results showed a decline in antioxidant defenses at 08:00 h, followed by a burst of pro-oxidant reactions, preparation of glutathione metabolism factors, and a tendency to decrease H2O2 and increase NO and H2S during the FAA. Most of the findings observed during the FAA were absent in response to one-day fasting. Hence, TRF involves concerted and sequential responses in liver pro-oxidant and antioxidant reactions, facilitating a redox-related circadian control that optimizes the metabolic utilization of nutrients, which differs from a response to a simple fast-feed cycle.